Key Statistical Concepts in Clinical Trials for Pharma - Turner, J. Rick. (SpringerBriefs in Pharmaceutical Science & Drug Development,, 2012)
This Brief discusses key statistical concepts that facilitate the inferential analysis of data collected from a group of individuals participating in a pharmaceutical clinical trial, the estimation of their clinical significance in the general population of individuals likely to be prescribed the drug if approved, and the related decision-making that occurs at both the public health level (by regulatory agencies when deciding whether or not to approve a new drug for marketing) and the individual patient level (by physicians and their patients when deciding whether or not the patient should be prescribed a drug that is on the market). These concepts include drug safety and efficacy, statistical significance, clinical significance, and benefit-risk balance.